2014
DOI: 10.1016/j.yhbeh.2014.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Effortful control and context interact in shaping neuroendocrine stress responses during childhood

Abstract: Trait and contextual factors can shape individual and group differences in hypothalamic-pituitary-adrenal (HPA) response to stress; but the ways in which these factors may interact with each other to modulate stress activity has rarely been examined. Here, we investigated whether the association between a temperamental self-regulatory trait – Effortful Control (EC) – and HPA axis stress response is moderated by type of laboratory stress in sixty-five children (35 boys). EC was measured at age 3 and 6 using age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…In addition, current contextual factors (e.g., actual controllability, novelty, perceived support) can moderate HPA axis activity (Dickerson and Kemeny, 2004; Levine, 2000). It is likely that developmentally-shaped psychosocial “trait” factors interact with such contextual factors to influence neuroendocrine responses in humans (e.g., Cosley et al, 2010; Mayer et al, 2014) and animals (Stocker et al, 2016). This interactive model is consistent with the function of the HPA axis to appropriately respond to acute and repeated stress experiences, based on current stressor characteristics and past environmental experiences.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, current contextual factors (e.g., actual controllability, novelty, perceived support) can moderate HPA axis activity (Dickerson and Kemeny, 2004; Levine, 2000). It is likely that developmentally-shaped psychosocial “trait” factors interact with such contextual factors to influence neuroendocrine responses in humans (e.g., Cosley et al, 2010; Mayer et al, 2014) and animals (Stocker et al, 2016). This interactive model is consistent with the function of the HPA axis to appropriately respond to acute and repeated stress experiences, based on current stressor characteristics and past environmental experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in adults it has been demonstrated that stress can lead to a shift in preference from healthy foods to foods with high‐added sugar and fats . Children with higher effortful control may have an improved ability to regulate their emotions and can better cope with stress over time, which could result in a lower preference for an unhealthy dietary intake .…”
Section: Discussionmentioning
confidence: 99%
“…Temperament has associations with both the autonomic nervous system (ANS; Spangler & Friedman, 2015) and the hypothalamic-pituitary-adrenal (HPA) axis (Mayer, Abelson, & Lopez-Duran, 2014)two fundamental stress response systems that, when dysregulated, may predispose individuals to increased risk of inflammation (Slavich & Irwin, 2014) and poor general health outcomes (McEwen, 2012). Two important dimensions of temperament that may influence risk for both depression (Hankin, 2015;Yap et al, 2011) and physiological processes related to disease (McEwen, 2012) are effortful control (EC) and negative emotionality (NE).…”
Section: Statement Of Contributionmentioning
confidence: 99%